Research on mathematical beliefs – the birth and growth of the MAVI group in 1995–2012 - Pehkonen, Erkki (NOMAD Nordic Studies in Mathematics Education, 2012)
In the 1980s the meaning of beliefs for teaching and learning aroused also to the consciousness of mathematics educators. Therefore, here it is firstly sketched the research field of mathematical beliefs, in order to understand why belief research has been a topic for an international research group for more than 30 years. The aim of the paper is to have a look at the history of MAVI and to describe its development within the years 1995–2012. A special look is given at the birth of the MAVI group in the middle of the 1990s and then its development through the last 18 years will be described. Also some statistics on the MAVI meetings and their participants are presented. And in the appendix the total list of the MAVI proceedings is documented.